2009
DOI: 10.1001/archdermatol.2008.574
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Repeated Exposures to Low-Dose UV Radiation on the Apoptosis of Peripheral Blood Mononuclear Cells

Abstract: To investigate whether repeated exposures to low-dose UV or solar-simulated radiation induce apoptosis of peripheral blood mononuclear cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
7
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 33 publications
4
7
0
Order By: Relevance
“…Caspase expression was not observed in WBCs following UV + R PRT, suggesting that these cells underwent an alternative caspase‐independent apoptotic pathway. Reports using varying doses of UV exposure suggested that WBCs generally undergo conventional apoptosis, that is, caspase activation, up regulation of GADD45α, CD95 (FAS/APO‐1), Bax, and/or p73, and poly–adenosine diphosphate ribose polymerase cleavage . There are, however, reports of caspase‐independent apoptosis occurring in WBCs in response to other stimuli, or in other cell types in response to UV exposure, providing some precedence for our findings .…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Caspase expression was not observed in WBCs following UV + R PRT, suggesting that these cells underwent an alternative caspase‐independent apoptotic pathway. Reports using varying doses of UV exposure suggested that WBCs generally undergo conventional apoptosis, that is, caspase activation, up regulation of GADD45α, CD95 (FAS/APO‐1), Bax, and/or p73, and poly–adenosine diphosphate ribose polymerase cleavage . There are, however, reports of caspase‐independent apoptosis occurring in WBCs in response to other stimuli, or in other cell types in response to UV exposure, providing some precedence for our findings .…”
Section: Discussionsupporting
confidence: 59%
“…21,22 UVB light induces apoptosis in many different mouse and human cell types by various mechanisms. [23][24][25][26][27][28][29][30] Different wavelengths and doses of UV light have different effects, with lower doses generally inducing apoptosis and higher doses inducing necrosis. 29 The cell death pathway induced also depends on the cell type and is related to the extent of DNA damage.…”
Section: Discussionmentioning
confidence: 99%
“…Apoptosis was monitored in healthy volunteers following whole body UVB or SSR with 0.7 personal minimal erythema dose (MED) on 10 consecutive days ( 10 ). The UVB exposure was equivalent to around 35 minutes outside on a clear sky day in mid-Europe around midday, and the SSR to 15 minutes under the same conditions.…”
Section: Effects Of Uvr On Pbmcsmentioning
confidence: 99%
“…It was enhanced in the PBMCs from the irradiated individuals, with SSR being more effective than UVB, possibly because the UVA emitted by the SSR can penetrate more effectively into the dermal microvasculature. In addition, SSR had a greater effect on reducing the expression of anti-apoptotic proteins while increasing that of pro-apoptotic proteins, leading to the suggestion that UVA induces apoptosis of lymphocytes via photosensitised oxygen radicals ( 10 ).…”
Section: Effects Of Uvr On Pbmcsmentioning
confidence: 99%
“…Furthermore, repeated UV radiation can cause DNA damage and apoptosis on human peripheral blood mononuclear cells, which indicate that sunlight exposure may cause internal diseases by affecting blood components. [37], [38] In addition, UV radiation is known to activate multiple signaling cascades, leading to inflammatory reactions. [39] Despite all of these possible pathways, the mechanisms of the association between actinic skin damage and mortality remain unclear.…”
Section: Discussionmentioning
confidence: 99%